SEIR Model to address the impact of face masks amid COVID‐19 pandemic. Issue 1 (15th June 2022) - Maged, Ahmed; Ahmed, Abdullah; Haridy, Salah; Baker, Arthur W.; Xie, Min
Abstract: Early in the pandemic of coronavirus disease 2019 (COVID‐19), face masks were used extensively by the general public in several Asian countries. The lower transmission rate of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in Asian countries compared with Western countries suggested that the wider community use of face masks has the potential to decrease transmission of SARS‐CoV‐2. A risk assessment model named Susceptible, Exposed, Infectious, Recovered (SEIR) model is used to quantitatively evaluate the potential impact of community face masks on SARS‐CoV‐2 reproduction number ( R 0 ) and peak number of infectious persons. For a simulated population of one million, the model showed a reduction in R 0 of 49% and 50% when 60% and 80% of the population wore masks, respectively. Moreover, we present a modified model that considers the effect of mask‐wearing after community vaccination. Interestingly mask‐wearing still provided a considerable benefit in lowering the number of infectious individuals. The results of this research are expected to help public health officials in making prompt decisions involving resource allocation and crafting legislation.